2021
DOI: 10.1302/0301-620x.103b11.bjj-2020-2130.r2
|View full text |Cite
|
Sign up to set email alerts
|

Second-look arthroscopic cartilage status is related to intermediate-term outcomes after medial opening-wedge high tibial osteotomy

Abstract: Aims To determine the relationship between articular cartilage status and clinical outcomes after medial opening-wedge high tibial osteotomy (MOHTO) for medial compartmental knee osteoarthritis at intermediate follow-up. Methods We reviewed 155 patients (155 knees) who underwent MOHTO from January 2008 to December 2016 followed by second-look arthroscopy with a mean 5.3-year follow-up (2.0 to 11.7). Arthroscopic findings were assessed according to the International Cartilage Repair Society (ICRS) Cartilage Rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Numerous studies have reported that OWHTO showed excellent clinical outcomes, slowed osteoarthritis progression, and delayed subsequent knee arthroplasty. 6,14,24,33,34…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have reported that OWHTO showed excellent clinical outcomes, slowed osteoarthritis progression, and delayed subsequent knee arthroplasty. 6,14,24,33,34…”
mentioning
confidence: 99%
“…Numerous studies have reported that OWHTO showed excellent clinical outcomes, slowed osteoarthritis progression, and delayed subsequent knee arthroplasty. 6,14,24,33,34 Conventionally, the target of adjusting the mechanical axis of the lower extremity is to pass through 62% to 62.5% from the medial edge of the proximal tibia, and previous studies reported favorable clinical outcomes and regeneration of articular cartilage of the medial femoral condyle after OWHTO targeting this point. 7,15,17 Despite accurate preoperative planning and fine surgical techniques, many OWHTOs result in under-or overcorrected alignment of the lower extremity as compared with the target point.…”
mentioning
confidence: 99%
“…Cartilage improvement after open-wedge high tibial osteotomy (OWHTO) is affected by age, sex, body mass index (BMI), preoperative cartilage status and postoperative limb alignment [1,8,11,13,16,24,26,33,34]. However the association between cartilage improvement after OWHTO and pain as well as knee function remains controversial [1,26], especially concerning medium-and long-term outcomes.…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 OWHTO improves the biomechanical environment of the knee joint by correcting the abnormal lower limb alignment with cartilage regeneration to produce the associated clinical outcomes and promote patient satisfaction. 3 - 7 Cartilage regeneration after high tibial osteotomy is influenced by multiple factors, including age, sex, body mass index (BMI), and postoperative knee alignment. 4 It should be noted, however, that the status of the articular cartilage at the time of second-look arthroscopy has not always been considered a predictor of clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%